Modifying Action Sounds Influences People's Emotional Responses and Bodily Sensations. (May 2014) - Tonetto, Leandro Miletto; Klanovicz, Cristiano Porto; Spence, Charles
We report an experiment designed to investigate the effect of modifying the sound of high-heeled shoes on women's self-reported valence, arousal, and dominance scores, as well as any changes to a variety of measures of bodily sensation. We also assessed whether self-evaluated personality traits and the enjoyment associated with wearing heels were correlated with these effects. Forty-eight women walked down a "virtual runway" while listening to four interaction sounds (leather- and polypropylene-soled high-heeled shoes contacting ceramic flooring or carpet). Analysis of the questionnaires that the participants completed indicated that the type of sonic interaction impacted valence, arousal, and dominance scores, as well as the evaluated bodily sensations. There were also correlations between these scores and both self-evaluated personality traits and the reported enjoyment associated with wearing high heels. These results demonstrate the effect that the sound of a woman's physical interaction with the environment can have, especially when her contact with the ground while walking makes a louder sound. More generally, these results demonstrate that the manipulation of product extrinsic sounds can modify people's evaluation of their emotional outcomes (valence, arousal, and dominance), as well as their bodily sensations.